SEAWEED SAP AS PRODUCTIVITY BOOSTER OF MAIZE - SHIKHA SINGH, M. K. SINGH, S. K. PAL, SAMINA PERWEEN, JAYANTI KUMARI, S. T. ZODAPE ARUP GHOSH (The Bioscan, 2015)
A field experiment conducted in the research farm of Birsa Agricultural University, Ranchi (JH) during kharif 2012-13 and 2013-14 with maize variety HQPM-1 in a randomized block design and replicated thrice, with two sources of seaweed sap namely Kappaphycus alvarezii and Gracilaria edulis at 6 concentrations (0.0, 2.5,5.0, 7.5,10.0 and 15.0% )with 100%RDF (150:60:40 kg N,P2O5 andK2O ha-1) and 4 concentrations (0.0, 7.5, 10.0 and 15%) with 50 % RDF,revealed that application of either 7.5% K sap or 5% G sap along with 100% RDF enhanced the grain yield by 34 and 30% respectively than application of 100% RDF alone (41.92 q ha-1). Application of 7.5% either of K sap or G sap along with 50% RDF produce similar grain yield (38.42 and 38.83 q ha-1 respectively) as that with 100% RDF alone and thereby saving 50% fertilizer need of the crop as well as maintained grain quality. Productivity of maize variety “HQPM-1” can be enhanced by more than 30% by the application of either 7.5%K sap or 5% G sap along with 100%RDF and can also save 50% fertilizer need of maize production with 50%RDF.